Vilka faktorer påverkar sjuksköterskestudenter att söka arbete inom Norrbotten läns landsting? - Shahgaldi, Anna (2016)
The aim of this thesis is to investigate the factors that influence the intention of nursing students at Luleå University of Technology (LTU) to apply for positions in Norrbottens läns landsting (NLL) after graduation. Based on Icek Ajzen’s (1985) Theory of Planned Behavior (TPB) the students’ attitudes, subjective norms and perceived behavioral control were examined. An electronic survey was filled out by 164 nursing students from all three grade levels at LTU. Five factors could predict the intent of nursing students to select NLL as a future employer. Of greatest significance was the family's opinion, followed by working conditions, the ability to develop, to live close to the people that matter and finally active nurses' opinions. Contrary to expectations, salary did not emerge as an important factor. The thesis ends with concrete strategy proposals about how NLL can improve and strengthen its appeal against newly graduated nurses from LTU. Validerat; 20160627 (global_studentproject_submitter)